More than tracks: how the cytoskeleton builds epithelia asymmetry - Almada, Evangelina (2018)
Epithelia are three-dimensional arrangements of cells organized into structures which delimit morphologically and physiologically different compartments. At the cellular level, epithelial cells are characterized by the presence of an apical pole, facing the lumen of an organ or the outer environment, and baso-lateral domains, involved in cell-extracellular matrix and cell-cell interactions. Each pole is characterized by its specific protein and lipid membrane composition, and its distinct assembly of cellular organelles. This polarized organization of cell components ensures the vectorial absorption and secretion of proteins and other molecules, which constitute the essential function of epithelia. Actin and microtubule cytoskeletons are also polarized in epithelial cells. This organization contributes to the de novo establishment as well as to the functional maintenance of epithelial polarity. In this article we delineate the central features of epithelial polarity and summarize the current knowledge on how actin and microtubule cytoskeletons contribute to epithelial organization.